2005
DOI: 10.1111/j.1523-5378.2005.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Template DNA Ratio can Affect Detection by Genus‐Specific PCR–Denaturing Gradient Gel Electrophoresis of Bacteria Present at Low Abundance in Mixed Populations

Abstract: The detection of Helicobacter species by genus-specific polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) was compared with that by species-specific PCR in murine intestinal samples. Results suggest that, in samples containing multiple Helicobacter species, genus-specific PCR-DGGE may fail to detect all Helicobacter species present and that this relates to the initial template DNA ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Thus, when the concentration of the DNA template of a particular bacterial species is signiWcantly higher than that of another species, the species with a lower concentration of the DNA template may not be detected by PCR-DGGE even if this "low" concentration is higher than the detection limit of single PCR. Zhang et al have reported that the minimum ratio was between 1:20 and 1:50 when the lower DNA was not detected in the PCR-DGGE using two bacterial DNA as the template [14]. Bollmann et al also performed a similar experiment and have shown the ratio at which the lower DNA would not be detected to be between 1:29 and 1:99 [13].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, when the concentration of the DNA template of a particular bacterial species is signiWcantly higher than that of another species, the species with a lower concentration of the DNA template may not be detected by PCR-DGGE even if this "low" concentration is higher than the detection limit of single PCR. Zhang et al have reported that the minimum ratio was between 1:20 and 1:50 when the lower DNA was not detected in the PCR-DGGE using two bacterial DNA as the template [14]. Bollmann et al also performed a similar experiment and have shown the ratio at which the lower DNA would not be detected to be between 1:29 and 1:99 [13].…”
Section: Discussionmentioning
confidence: 91%
“…PCR is known to have high detection sensitivity. However, it has been reported that the initial template DNA ratio in a sample obtained from a mixed population may aVect the detection of bacterial species that have low levels of abundance by genus-speciWc PCR-DGGE [13,14]. Thus, when the concentration of the DNA template of a particular bacterial species is signiWcantly higher than that of another species, the species with a lower concentration of the DNA template may not be detected by PCR-DGGE even if this "low" concentration is higher than the detection limit of single PCR.…”
Section: Discussionmentioning
confidence: 99%
“…For bacteria, changes were real but not clearly correlated with grape development. This may result from a variation of species ratio and the detection of highly abundant species in a mixed population (Zhang et al 2005). Climatic variations (temperature, humidity, UV radiation), agrochemical applications, and viticultural practices such as leaf thinning, are several factors that are liable to influence the berry micro-environment and consequently the microbial ecosystem on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the potential to detect a specific taxon can be improved by using group-specific primers that can narrow the size of the target population. Even when using a genus-specific primer, however, the template DNA ratio may still affect the DGGE-based detection of certain species that are underrepresented in a mixed community sample [128]. Although poorly studied for SDE-based community fingerprinting of human microbiota, multiple displacement amplification (MDA) may provide another strategy to enhance the detection level especially in biopsy samples with lower bacterial counts.…”
Section: Limitations and Potential Pitfallsmentioning
confidence: 99%